Law and Religion in Ireland, 1700-1970
XIII, 399 p. 1 illus.
Keywords: This book focuses, from a legal perspective, on a series of events which make up some of the principal episodes in the legal history of religion in Ireland: the anti-Catholic penal laws of the late seventeenth and early eighteenth century; the shift towards the removal of disabilities from Catholics and dissenters; the dis-establishment of the Church of Ireland; and the place of religion, and the Catholic Church, under the Constitutions of 1922 and 1937. Kevin Costello is Associate Professor at the Sutherland School of Law, University College Dublin, Ireland. He has previously published Law and the Family in Ireland, 1800-1950 (Palgrave, 2017). Niamh Howlin is Associate Professor at the Sutherland School of Law, University College Dublin, Ireland. She has previously published Law and the Family in Ireland, 1800-1950 (Palgrave, 2017).